Politics and culture : essays in honour of Serajul Islam Choudhury - Alam, Fakrul; Azim, Firdous; University of Dhaka. Department of English (Dhaka : Dept. of English, University of Dhaka, 2002)
Contributed articles.
Includes bibliographical references.
Keywords: Politics